Tribology for Scientists and Engineers From Basics to Advanced Concepts - Menezes, Pradeep L.; Nosonovsky, Michael.; Ingole, Sudeep P.; Kailas, Satish V.; Lovell, Michael R. (Springer New York : Imprint: Springer, 2013)
This book details a comprehensive overview of tribology.  General information on how tribology is approached in various related areas of research, both experimental and computational is provided. The book contains up-to-date data and describes current technologies.